UR_GERICHTE 04/05 18 vom 24. Mai 2005 - UR Obergericht (2005)
Strafprozessordnung. Art. 6 Ziff. 2 EMRK. Art. 29 Abs. 2, Art. 32 Abs. 1 BV. Art. 249 BStP. Art.188 Abs. 2, Art. 227 Abs.1 StPO. | Strafprozessordnung. Art. 6 Ziff. 2 EMRK. Art. 29 Abs. 2,